Strategi Ekonomi Seniman Kethoprak Balekambang di Masa Pandemi Covid-19 melalui Media Baru - Iswahyudi Tejo Yuwono; Huda Maulana Kurnia; Muhammad Wahyu Tri Nugroho; Magfireza Akbari (Ekonomis: Journal of Economics and Business, 2023)
This paper aims to describe how the Balekambang kethoprak artists maintain their economic status and continue to work in a space that no longer exists. What kind of management strategy will be adopted so that the pot remains upright and the idealism of work is maintained. There must be a specific strategy for various sectors of human activity, especially in physical activity. This research is an empirical qualitative research, with the subjects being artists who are members of the Balekambang kethoprak artist group. Data collection techniques were observation and direct interviews with the subject on the spot. Data mining guides are management theory, as they are implemented to maintain self-life and art life. The results of the study found that the artists displayed a management approach to survive. Supporting oneself and living the arts is pursued by planning, organizing, actuating, and controlling management strategies. In the end, digital technology as a new media continues to be developed as a form of adaptation to society during a pandemic. One of the activities adapted to digital media is an art exhibition.